Pengaruh Kinerja Lingkungan Terhadap Kinerja Keuangan Dengan Pengungkapan Corporate Social Responsibility (CSR) Sebagai Variabel Intervening - Putra, Yudi Partama (Universitas Muhammadiyah Palembang, 2017)
ABSTRACT This research aims to know (1) the influence of environmental performance against financial performance, (2) the influence of environmental performance against disclosure of CSR, (3) the influence of disclosure of CSR against financial performance and (4) the influence of corporate social responsibility disclosure mediate the relationship between environmental performance to financial performance at manufacturing companies listed in BEI. The population in this study are all the manufacturing companies listed on the BEI and participate in the PROPER in 2013-2016. The sample of this research totaled 160 manufacturing companies, with the method of data collection using a purposive sampling and the type of data used is secondary data. This research uses statistical data analysis techniques of descriptive, classical assumption test, regression analysis, path analysis (Sobel Test) and test the hypothesis. The results show that the performance of the environment has no effect on the financial performance (0.0826 > 0,05), environmental performance does not have an impact on disclosure of CSR (0,47 > 0,05), CSR disclosure has positive and significant effect on the financial performance (0,0115 < 0,05). Hypotheses are tested using sobel test and show that CSR can not mediate the relationship between environmental performance and financial performance (0.652602 < 1,66). It is concluded that the corporate social responsibility (CSR) disclosure is not an intervening variable between environmental performance and financial performance.